Worship and religious motivation of Ekayana Dharma Budhi Bhakti junior high school students’ north Jakarta - Poni Pania; Komang Sutawan; Ayu Andriyaningsih (International Journal of Science and Applied Science: Conference Series, 2025)
This study aims to analyse the influence of Puja Bhakti on the religious motivation of students at Ekayana Dharma Budhi Bhakti Junior High School, North Jakarta. Puja Bhakti is believed to cultivate a disciplined mind capable of developing kindness and wisdom, thereby reducing the tendency for regret. Religious motivation is understood as an internal drive that compels individuals to practice religious teachings not only on a cognitive level but also through real-life application. This research employed a quantitative approach using a survey method, with questionnaires distributed to a sample of students as the primary instrument for data collection. Data were analysed using regression analysis to determine the extent to which participation in Puja Bhakti influences students' religious motivation. The findings reveal that students' engagement in Puja Bhakti falls into a high category, with a participation rate of 74.7%. The results indicate a significant positive influence of Puja Bhakti on students' religious motivation. This suggests that active participation in Puja Bhakti can substantially enhance students' commitment to practising their faith. The novelty of this research lies in its focused exploration of the relationship between Puja Bhakti and the development of religious motivation, distinguishing it from prior studies. Consequently, this study contributes meaningfully to the field of religious education by emphasising the role of structured ritual practices in nurturing students' spiritual growth. Moreover, the findings underscore the importance of ritual worship as a practical and experiential strategy for schools to instil religious values effectively within the learning environment.